2008
DOI: 10.2223/jped.1821
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the neonatal outcomes of the kangaroo mother method in Brazil

Abstract: Resultados: Na análise ajustada (para peso de nascimento, idade gestacional, Score for Neonatal Acute Physiology Perinatal Extension II, Neonatal Therapeutic Intervention Scoring System, idade e escolaridade maternas), o tempo médio de internação (p = 0,14) e intercorrências clínicas na unidade intermediária ou canguru foram iguais entre os grupos. Peso (p = 0,012), comprimento (p = 0,039) e perímetro cefálico (p = 0,006) com 36 semanas de idade gestacional corrigida foram menores nas unidades canguru. As unid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
2
5

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 22 publications
4
7
2
5
Order By: Relevance
“…The factors that determine the growth of preterm infants are still poorly understood, but there is data showing that it remains considerably insufficient ( 23 ) . Despite being one of the mains pillars of the KM, the frequency of exclusive breastfeeding at hospital discharge in the present study was below that found by other authors who analyzed PTNBs assisted with the KM ( 9 , 21 , 27 ) . Perhaps the low frequency of this practice has contributed to the rate of preterm infants classified as small for corrected age at hospital discharge.…”
Section: Discussioncontrasting
confidence: 93%
See 2 more Smart Citations
“…The factors that determine the growth of preterm infants are still poorly understood, but there is data showing that it remains considerably insufficient ( 23 ) . Despite being one of the mains pillars of the KM, the frequency of exclusive breastfeeding at hospital discharge in the present study was below that found by other authors who analyzed PTNBs assisted with the KM ( 9 , 21 , 27 ) . Perhaps the low frequency of this practice has contributed to the rate of preterm infants classified as small for corrected age at hospital discharge.…”
Section: Discussioncontrasting
confidence: 93%
“…The most prevalent maternal diseases were those that induced premature birth ( 20 ) . The mean gestational age of the sample was similar to that described by other authors ( 21 ) in a study that assessed the results of the KM in Brazil, while the length of stay in the NICU was much lower in the present study, and the length of stay at the Kangaroo Ward was similar.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our findings indicated that the mothers who performed KMC in NICU for their preterm infants had more exclusive breastfeeding at the time of hospital discharge (62.5% vs. 37.5%).%) than those who did not perform KMC. This result is similar with Suman (13), and Bicalho (15) study. Suman reported that mothers who had more KMC had more exclusive breastfeeding (98% versus 79%) (16), and Bicalho reported that the kangaroo units exhibited superior performance in relation to exclusive breastfeeding at discharge (69.2 vs. 23.8%).…”
Section: Discussionsupporting
confidence: 92%
“…There is growing evidence that the KM brings benefits that are both physiological [2-7], such as improvement in the vital signs, oxygenation of the brain and reduction in the pain response, and behavioral [1,8,9], such as improved sleep and less crying in the preterm newborn, and also improves adherence to and duration of maternal breastfeeding [4,9,10] and mother-child bonding [1]. This method is also associated with a reduction in time spent in hospital and in mortality among preterm newborns [4,11].…”
Section: Introductionmentioning
confidence: 99%